ANALISIS TINGKAT KEPUASAN KONSUMEN TERHADAP KUALITAS PELAYANAN DI INDOMARET DELIVERY CIKARET KODE TOKO (TA5P) KECAMATAN CIBINONG KABUPATEN BOGOR - Siti Nurkilah; ., Mujito; Adyas, Dasmansyah (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2022)
This study aims to determine the level of service performance of Indomaret Delivery Cikaret Toko Kode TA5P, Cibinong District, Bogor Regency as well as to determine customer satisfaction with service quality and to find out what factors must be improved in order to become consumer satisfaction for Indomaret Delivery Cikaret Toko Kode TA5P, Cibinong District, Bogor Regency. . The results of the study show that: (1) The level of service quality is very good in meeting consumer satisfaction Indomaret Delivery Cikaret Toko Kode TA5P is at indicator 14, the total value is 429 from the total maximum value of 500 (5 x 100). (2) The level of customer satisfaction is very good in the quality of service provided by Indomaret Delivery Cikaret Toko Kode TA5P in indicator 2, a total value of 443 is obtained from the total maximum value of 500 (5 x 100). (3) Overall the highest level of conformity in indicator 4 obtained a level of conformity of 106.23%. While the smallest level of conformity is on indicator 8, which is 92.63%. (4) The level of service quality that is a top priority and must be maintained is in quadrants I and II, especially quadrant I.